Phylogenetic of Ornamented Chilli Based on the Fruit Morphology and Molecular Marker using OPA-12 Primer - Rejeki Siti Ferniah; Endang Kusdiyantini; Nurhayati Nurhayati (Agric, 2018)
There are many varieties of ornamental chilli that may different from their ancestor and cause genetic variability. This research aims to determine the relationship of ornamental chillies in Indonesia based on their fruit morphology and RAPD-PCR. Morphological was analysed by description method, while molecular was analysed by RAPD-PCR using OPA 12 primer. Result showed that Katty, Naga Morich, Big Black Mama, and Yellow Primo were Capsicum chinense based on their morphology and RAPD-PCR using OPA-12 primer.